Macroeconomic Variables and Indian Stock Market:A Relationship Analysis - Saluja, HS (International Journal of Computer Sciences and Engineering, 2025)
The Indian Stock Market showed a tremendous growth during last two decades. The SENSEX Index of Bombay Stock Exchange had reached to 38000 level points in August, 2018 which is its life time high level. It raises empirical questions regarding the fundamental connection between stock price and key macroeconomic indicators. The present study is an attempt to find the impact of macroeconomic variables on Indian Stock Market, with respect to SENSEX Index of Bombay Stock Exchange. The macroeconomic variables considered for the purpose of the study include Foreign Institutional Investors, Domestic Institutional Investors, Exchange Rates, Interest Rates and Inflation etc. The monthly closing values were taken for analysis for the period from January 2012 to August 2018. The Regression Analysis, Co-relation Analysis and Granger Causality Test will be applied to examine the relations between the selected variables.